TIKTOK DAN PERUBAHAN PENDIDIKAN, SOSIAL DAN POLITIK - Deby Indah Armayanti Pasaribu; Nurul Mursida Siregar; Rika Amelia Pulungan; Siti Arbiyah Nasution; Sholeh Fikri (Program Studi Komunikasi dan Penyiaran Islam, 2026)
This study discusses the role of TikTok as a social media platform that influences changes in the fields of education, society, and politics within contemporary digital culture. Using a descriptive qualitative approach, the research explores how TikTok serves as a new space for creative learning, digital identity formation, and participatory political communication. The findings reveal that TikTok functions as a visual learning medium that bridges the gap between formal education and the learning style of younger generations. Socially, the platform fosters the emergence of digital communities and fluid new identities while also presenting ethical challenges such as viral culture and social pressure. In the political sphere, TikTok transforms public communication patterns into more emotional and image-based forms, requiring a more critical level of digital literacy. Therefore, digital literacy becomes the key to ensuring that TikTok is utilized for empowerment rather than mere entertainment